2019
DOI: 10.1177/1461348419861837
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the transient response of a speed-varying rotor with sudden unbalance and its application in the unbalance identification

Abstract: It is well known that the sudden unbalance is harmful for rotor systems, since it is in huge amount and has a strong impact. Thus, it is difficult to identify the unbalance from the sudden unbalance response of rotor and very few studies have been done on this topic. This paper focuses on the transient response characteristics of the speed-varying rotor when the sudden unbalance occurs, and the inherent correlation between the unbalance and the transient characteristic quantity. First, different time-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The results showed the interaction between different faults on the vibration behavior of system. The transient response of the speed-varying rotor in the presence of occurring sudden unbalance fault was studied by Xia et al and the results indicated a novel method for unbalance identification using the transient response [11]. A study on the transient analysis of a complex rotor with nonlinear bearings and dampers was studied by Cao [12].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed the interaction between different faults on the vibration behavior of system. The transient response of the speed-varying rotor in the presence of occurring sudden unbalance fault was studied by Xia et al and the results indicated a novel method for unbalance identification using the transient response [11]. A study on the transient analysis of a complex rotor with nonlinear bearings and dampers was studied by Cao [12].…”
Section: Introductionmentioning
confidence: 99%
“…Identifying rotor unbalance without test runs is the current trend [15]. This approach can be divided into two types: a method with external excitation and a method without external excitation.…”
Section: Introduction 1background and Formulation Of The Problemmentioning
confidence: 99%
“…By using run-up and shutdown process, Sinha et al [13] proposed a method for speed-variant machines to calculate unbalance and misalignment of a flexible rotary machine. There have also been various kinds of modalbased balancing methods developed during the last few years [14][15][16][17]. The application of these methods have been studied for industrial-sized equipment [18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%